A CONTRAST PATTERN OF REEF FISH SPECIES DIVERSITY AND DISTRIBUTION USING ENVIRONMENTAL DNA (eDNA) METABARCODING IN LONGITUDINAL DISTANCE FROM JAKARTA BAY (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
The existence of reef fish is certainly closely related to the existence of reefs coral because the ecosystem is a habitat for reef fish. Coral reefs are ecosystems that are commonly found on small islands in the tropics including the Seribu Islands. The Seribu Islands are a group of 110 islands located off the coast of Jakarta and up to 80 kilometers north of the Java Sea. In this study, we examined the species distribution and diversity of reef fish species on two different distance location in Jakarta Bay using environmental DNA (eDNA) metabarcoding analysis from two sites which are Untung Jawa Island and Harapan Island. The 4L eDNA seawater samples were collected at a depth of 8-9 meters at each site and then analysis using specific primer (MiFish U) of 12S rRNA. Overall, the higher species richness was found on Harapan Island (52 species) followed by Untung Jawa Island (11 species). The Shannon-Wiener Index also showed Harapan Island has higher reef fish diversity based on three taxonomic level (family, genus, and species). There were only five mutual reef fish species found in the two locations, namely Atherinomorus aetholepis, Auxis thazard, Cephalopholis sexmaculata, Epinephelus chlorostigma, and Plectropomus areolatus. The results of these findings in this current study are in line with anthropogenic pressure different where Untung Jawa Island is the closer one to Jakarta Bay than the Harapan Island that located relatively far from Jakarta Bay.